Theoretical stability derivatives of a highly swept delta wing and slender body combination - Nonweiler, T. (College of Aeronautics, Cranfield, 1951)
The stability derivatives of a delta wing of small aspect ratio, mounted on a cylindrical body with a slender pointed head, are derived by considering the flow in planes perpendicular to the body axis to be uninfluenced by the change in the streamwise component of the air velocity (the so-called ‘slender body’ theory).